A new fractal model on fluid flow/heat/mass transport in complex porous structures. (December 2020) - Wu, C.Q.; Xu, H.J.; Zhao, C.Y.
Highlights: A new fractal theoretical model is established to predict the transport in complex porous media. Solutions to the transport parameters of single-phase fluid in porous media are derived. Solutions to the transport parameters of two-phase fluid in porous media are derived. Analytical results of the proposed model are compared with the previous model. The predicted results of the theoretical model agree well with experimental data. Abstract: A new fractal theoretical model with periodic pore morphology, which idealizes the pore channels of the porous media as gourd-shaped structure, is established to model the transport in complex porous media. Based on the fractal model, the flow/thermal/mass transport properties of single-phase fluid and two-phase fluid flowing through porous structures are predicted, and analytical solutions to the permeability, thermal conductivity, diffusion coefficient of single-phase fluid in porous media, and the permeability, and the thermal conductivity of two-phase fluid in unsaturated porous media are derived. The analytical results of the proposed model for predicting the single-phase gaseous flow, heat and mass transfer in porous media are compared with the previous model data based on the idealized tubule-shaped structure of the real pore channels in porous media, which shows that the previous tubule-shaped structure is a limiting case of the present gourd-shaped structure. Analytical expressions of absolute permeability, relative permeability, and effective thermal conductivity of two-phase flow and heat transport in unsaturated porous media are derived for the present model and the previous tubule model. A parametric analysis is performed for presenting the effects of the structural parameters and fluid properties on the effective thermal conductivity, permeability and effective diffusion coefficient predicted. Meanwhile, the results show that the predicted data of the theoretical model are in good agreement with experimental data. The present study is significant for enhancing the flow, heat and mass transfer in accurately predicting transport properties of real porous media applications, and can provide an important parameter basis and guidance for the design of the transport system incorporating porous media.